Closed Kinetic Chain Exercise Revolutionizes Knee Osteoarthritis Management: Latihan Rantai Kinetik Tertutup Merevolusi Manajemen Osteoartritis Lutut - Trisnita Yulianti; Soffil Yudha Mulyadi (Academia Open, 2024)
Knee osteoarthritis, prevalent among the elderly, poses challenges due to cartilage erosion and bone changes. This study examines the effectiveness of adding closed kinetic chain exercise to conventional modalities for improving knee functional activity. Using a quasi-experimental design, knee functional improvement was compared between groups receiving closed kinetic chain exercise and conventional modalities. Results show significant improvement in knee function with closed kinetic chain exercise, suggesting its potential as a safe and beneficial intervention for knee osteoarthritis management. Highlight: Elderly Challenge: Knee osteoarthritis impacts functional ability, requiring effective interventions. Exercise Efficacy: Closed kinetic chain exercise enhances knee function significantly. Comparative Study: Quasi-experimental design reveals exercise effectiveness versus conventional modalities. Keyword: Knee osteoarthritis, closed kinetic chain exercise, functional activity, elderly, intervention